From mononuclear to polynuclear: copper and zinc complexes obtained from polypyridylamine ligands related to tris(2-pyridylmethyl)-amine (tmpa). Issue 11 (3rd July 2018) - Beitat, Alexander; Becker, Jonathan; Xu, Jing-Yuan; Brombach, Christoph-Cornelius; Becker, Sabine; Kelm, Harald; Walter, Olaf; Würtele, Christian; Schindler, Siegfried
Abstract: Copper(I)/(II) complexes and a zinc compound with polypyridylamine ligands (related to the tripodal ligand tris(2-pyridylmethyl)amine, tmpa ) were synthesized. Crystallographic characterization was possible for most of the complexes obtained. The different structures of the complexes allowed some insight into the basic understanding of the design of coordination polymers. Depending on ligand, solvent or anion, either mononuclear, dinuclear or polynuclear complexes were obtained. Graphical Abstract: